2023
DOI: 10.3390/agriculture13030602
|View full text |Cite
|
Sign up to set email alerts
|

Strategies Used to Reduce Methane Emissions from Ruminants: Controversies and Issues

Abstract: Methanogenesis plays a crucial role in the digestive process of ruminant animals. During this process, methanogenic archaea produce methane as a byproduct of their metabolism. However, the production of methane by ruminants is also a significant contributor to greenhouse gas emissions. Methane is a potent greenhouse gas that has a 28-fold greater global warming potential than carbon dioxide. Around 15% of all anthropogenic greenhouse gas emissions are generated by livestock. Therefore, reducing methane emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 165 publications
0
26
0
Order By: Relevance
“…The digestion process in ruminants produces gases as a byproduct of metabolism. The limitation of gas emissions and, in particular, CH 4 production is highly desirable [ 4 ]. However, reducing CH 4 emissions can negatively affect the efficiency of feed use efficiency [ 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The digestion process in ruminants produces gases as a byproduct of metabolism. The limitation of gas emissions and, in particular, CH 4 production is highly desirable [ 4 ]. However, reducing CH 4 emissions can negatively affect the efficiency of feed use efficiency [ 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the latest report published in April 2023 by the Intergovernmental Panel on Climate Change reported that agriculture accounts for 22% of global greenhouse gas emissions, rendering the agricultural sector one of the leading contributors to global warming [ 2 , 3 ]. Different strategies, such as dietary modification, genetic selection, microbiome manipulation, and feed additives, such as plant secondary metabolites, CH 4 inhibitors, lipids, essential oils, and algae, are used to reduce the enteric emissions of gases like CH 4 or carbon dioxide during the production of food products [ 4 ]. The general importance of minerals in the body is known and indisputable.…”
Section: Introductionmentioning
confidence: 99%
“…Methanogenesis has been playing a significant role in digestion, producing methane as a byproduct of metabolism in ruminant animals, and this process has been a significant contributor to greenhouse gas emissions [ 52 ]. Various mitigation strategies have been developed to reduce methane (CH 4 ) emissions, including dietary modifications involving lipids, essential oils, and algae [ 53 , 54 ].…”
Section: Alternative Feed Resources In Small Ruminant’s Nutritionmentioning
confidence: 99%
“…However, factors such as the physiological stage of the animal, the composition of the basal diet’s lipids and other nutrients, and the fatty acid profile of the supplemental oil can influence the maximum oil inclusion in ruminant diets. High lipid concentrations (>6% DM) in feed can reduce feed and fiber digestibility, potentially increasing OM [ 52 ].…”
Section: Alternative Feed Resources In Small Ruminant’s Nutritionmentioning
confidence: 99%
“…Methane, a potent greenhouse gas with 28× the global warming potential of CO 2 , is a critical target for reduction given this compound's high global warming potential. , Agricultural production of ruminant livestock is responsible for 24% of global methane emissions. Methane has a short atmospheric lifetime (8.6 years), so effective mitigation strategies could have a large impact in a relatively short period of time. Consequently, the agricultural sector faces an urgent challenge to reduce ruminant methane emissions, especially with an anticipated 80% increase in demand for beef by 2050 .…”
Section: Introductionmentioning
confidence: 99%